Unrolling the Systematics of a Southeastern Pacific Chiton - Christian M. Ibáñez; Boris Sirenko (Taxonomy, 2024)
The species Chiton echinatus was first described by Barmes in 1824. Subsequently, it has been allocated to several widely distributed genera (e.g., Acanthopleura, Enoplochiton, Mesotomura) within the subfamily Acanthopleurinae. In order to resolve this species’ taxonomic uncertainty, specimens were collected throughout its entire distribution (i.e. from Peru and Chile) and subjected to a series of morphological and phylogenetic analyses. Scanning electron microscopy was used to improve this species’ morphological description, whereas publicly available sequences were used to infer its phylogenetic position. Morphological and phylogenetic analyses suggest that this species merits its own genus, endemic to the Southeastern Pacific. Of the aforementioned genera, Mesotomura appears to be the most appropriate designation. Therefore, it is proposed that the name Mesotomura echinata be restored, and the range of this species be extended to 39° S.